Note from the Editor - Schutte, Corne (The South African Journal of Industrial Engineering, 2025)
"Excellence is never an accident. It is always the result of high intention, sincere effort, and intelligent execution." Aristotle The Southern African Institute for Industrial Engineering (SAIIE) Annual Awards Ceremony took place on 21 August at the historic Country Club Johannesburg, where two journal-specific awards were presented: The SAIIE Award for the Best Industrial Engineering Paper, published in the South African Journal of Industrial Engineering (SAJIE), was this year presented to Paul Burger, a Master’s student at North-West University, for his article “Future Mines’ Compressed Air Planning Using Digital Twin Simulations.” The paper was co-authored with Dr Jan Vosloo and Dr Jean van Laar. Read the article here: https://doi.org/10.7166/35-3-3094. The SAJIE Editor Award was presented to our meticulous Technical Editor, Eldon Burger from Stellenbosch University. Eldon has fulfilled this critical role with exceptional efficiency, often working quietly behind the scenes. The consistently high technical quality of every article published in SAJIE is a direct result of his dedication and hard work. Our upcoming issue will be a special edition, featuring the best submissions from leading conferences in South Africa. The review and selection process for the SAIIE conference has already been completed, and we look forward to showcasing the innovative research and fresh thinking that emerged from these events. This edition has a total of 15 articles, with 13 articles from authors with South African connections and the balance from international authors. If you have suggestions on how we can take this journal forward, please let me know. Corne Schutte Editor